A Study of Recent Trends and Tehnologies on Openstack Cloud Computing - Sabapathi, V; Kamalanaban, E; Vishwath, R; N.Lokesh, K (International Journal of Engineering and Technology, 2018)
Cloud computing is internet based access resources with low cost computing. On demand resources, elasticity, resources pooling are key characteristics of cloud computing. In this paper mainly discussing various trends of cloud computing and technologies, service providers, services. Cloud basic core methodology, service providersÂ Â with recent technologies are analyzes. Cloud core and concurrent development cloud services and their characteristics are described. Recent tools for applications development for cloud implement technologies. Basics of cloud computing, deployment models, service models, service provider techniques are analyzed.Â Â